(untitled) (Revista de Artes Marciales Asiáticas, 2016)
This article, which falls within the scope of the sociology of sport, aims to study the perspective and understanding of martial and combat sports practitioners, especially of karate, in Portugal, on the concept of “Budo”. For this study, we used an extensive methodology and applied various techniques of social research (semi-directive interview, questionnaire survey). The sample was composed of 244 advanced karateka (brown and black belt) at the national level. The results showed that karate practitioners conceive their practice as an expression of Budo, reproduced in a dominant way by teaching staff (trainers), through images, symbols and values. Karatekas gave special importance to the codes and standards of conduct associated with the ethical principles of Budô and the maintenance of the rites and symbols from the country of the Rising Sun. Karatekas who most valued Budo practiced the same karate style, therefore, the study may not be generalized to all practitioners of karate.